First experience with the Hugo™ robot‐assisted surgery system for endometriosis: A descriptive study - Rikke Groth Olsen; Dorthe Hartwell; Torur Dalsgaard; Mette Elkjær Madsen; Flemming Bjerrum; Lars Konge; Andreas Røder (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The Medtronic Hugo™ Robot‐assisted Surgery (RAS) system was recently approved for clinical use. We explored the safety and feasibility of this system for endometriosis surgery. The primary outcome was safe case completion without major surgical complications (Clavien–Dindo grade ≤2) and no conversion to open surgery or laparoscopy. Material and methods Surgeries for endometriosis performed at the Department of Gynecology, Rigshospitalet, on the Medtronic Hugo™ RAS system were included. Two experienced robotic surgeons performed all surgeries with their usual robotic team. The variables included were patient demographics, peri‐ and postoperative data, complications and 30‐day readmission rate. We used the IDEAL framework 1/2a for surgical innovation in this descriptive study. Results The first 12 patients were included. All cases were completed without intraoperative complications or conversion. Four patients experienced Clavien–Dindo grade 1 postoperative complications. No patients were re‐admitted within 30 days. Median docking time (17 minutes), console time (87.5 minutes), blood loss (40 mL) and length of hospital stay (1 day) were acceptable compared with previous literature. Conclusions In this pilot study, we found the Medtronic Hugo™ RAS system safe and feasible for robot‐assisted surgery for endometriosis. The advent of new robotic systems is welcomed to accelerate the development of technology that will advance surgical care for patients across the globe.